The sportsman readjustment after transcontinental flight: a study on marathon runners - Montaruli, A.; Roveda, E.; Calogiuri, G.; La Torre, A.; Carandente, F. (The Journal of Sports Medicine and Physical Fitness, 2009)
AIM: The aim of the study was to evaluate the synchronizing effect of physical activity on the rest-activity cycle after a flight across different time zones, investigating the parameters linked to sleep. The purpose of this study is to evaluate the synchronizing effect of physical activity on the sleep-activity parameters after a flight across different time zones. METHODS: Eighteen volunteers flew from Milan to New York for the 2007 New York City Marathon. A training program, that consisted of running sessions three times a week for one month, was planned for the twelve athletes that participated in the marathon. The athletes were divided in two groups: Morning Training Group (MTG), trained from 7:00 to 9:00; Evening Training Group (ETG) from 19:00 to 21:00. The Control Group (CG), of 6 non-athletes, did not train before the flight and did not participate in the marathon. In New York, both groups of athletes trained in the morning. Two Actigraph monitoring sessions were performed in all three groups, before the Milan-New York flight and during the stay in New York. The actigraphy made it possible to calculate sleep and activity-specific parameters; sleep and activity patterns were continuously monitored using an actometer on the wrist of the non-dominant hand. RESULTS: Sleep analysis done on the first night in New York showed a significant difference (P<0.05) in the Movement and Fragmentation Index (MFI) between MTG and ETG. In CG and MTG, the MFI increased after the flight, while in ETG, the MFI decreased. Activity analysis demonstrated that, in ETG, evening physical activity in Milan associated with morning activity in New York produced a shift in the Cosine Peak of the rhythm of activity. CONCLUSIONS: Physical activity can have a positive effect both on sleep, by improving quality, as well as on the circadian rhythm of activity, by encouraging re-synchronization after the flight.